Pesticides and Chapada Diamantina: consumption and health of small farmers in Mucugê and Ibicoara, Bahia (Research, Society and Development, 2020)
The objective of the work was to characterize the socioeconomic profile of small rural producers in the Mucugê and Ibicoara agricultural sector, Chapada Diamantina, Bahia, Brazil, as well as to investigate the main factors of exposure of producers to pesticides and to identify the main chemical products used in production. To this end, we conducted a cross-sectional study, using a semi-structured questionnaire, taking into account the classification of small producers. Thus, 31 rural producers were identified and interviewed, with a predominant male presence and low level of education. Rural producers receive little assistance from official agencies of technical assistance and rural extension, and often adopt inadequate practices and procedures regarding guidance on the prescription, specificity, handling and use of pesticides. Thus, the high prevalence in the use of pesticides, inadequate guidance as to its specificity of action for the control of pests and diseases and inadequate occupational health measures can accentuate the risks of human and environmental contamination.